Atomic-scale spin sensing with a single molecule at the apex of a scanning tunneling microscope - Verlhac, Benjamin (2019)
Recent advances in scanning probe techniques rely on the chemical functionalization of the probe-tip termination by a single molecule. The success of this approach opens the prospect of introducing spin sensitivity through functionalization by a magnetic molecule. We used a nickelocene-terminated tip (Nc-tip), which offered the possibility of producing spin excitations on the tip apex of a scanning tunneling microscope (STM). When the Nc-tip was 100 picometers away from point contact with a surface-supported object, magnetic effects could be probed through changes in the spin excitation spectrum of nickelocene. We used this detection scheme to simultaneously determine the exchange field and the spin polarization of iron atoms and cobalt films on a copper surface with atomic-scale resolution.